2001
DOI: 10.1073/pnas.211443198
|View full text |Cite
|
Sign up to set email alerts
|

Role of p42/p44 mitogen-activated-protein kinase and p21 waf1/cip1 in the regulation of vascular smooth muscle cell proliferation by nitric oxide

Abstract: The purpose of this study was to determine the involvement of the p42͞p44 mitogen-activated protein kinase (MAPK) pathway and induction of p21 waf1/cip1 in the antiproliferative effects of nitric oxide (NO) on rat aortic smooth muscle cells (RASMC). NO, like ␣-difluoromethylornithine (DFMO), interferes with cell proliferation by inhibiting ornithine decarboxylase (ODC) and, therefore, polyamine synthesis. S-nitroso-N-acetylpenicillamine or (Z)-1-[N-(2-aminoethyl)-N-(2-aminoethyl)-amino]-diazen-1-ium-1,2-diolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
35
1
2

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 34 publications
4
35
1
2
Order By: Relevance
“…This relationship between nitrite and p21 is suggested in vivo, where p21 was shown to be upregulated within the limited neointima following nitrite treatment. Previously published studies focusing on the inhibition of SMC proliferation by NO have also shown it to be dependent upon p21 (40)(41)(42). Our findings support the hypothesis that the effect of nitrite on SMC proliferation is exerted via NO-mediated downstream signaling.…”
Section: Figuresupporting
confidence: 89%
See 1 more Smart Citation
“…This relationship between nitrite and p21 is suggested in vivo, where p21 was shown to be upregulated within the limited neointima following nitrite treatment. Previously published studies focusing on the inhibition of SMC proliferation by NO have also shown it to be dependent upon p21 (40)(41)(42). Our findings support the hypothesis that the effect of nitrite on SMC proliferation is exerted via NO-mediated downstream signaling.…”
Section: Figuresupporting
confidence: 89%
“…Waf1/Cip1 . Others and we have previously illustrated (40)(41)(42) that NO-induced inhibition of proliferation in SMCs is dependent on the upregulation of the cyclin-dependent kinase inhibitor p21 Waf1/Cip1 . In order to determine whether sodium nitrite increases p21 expression, we treated SMCs with or without sodium nitrite (0-100 μM) or DETA-NONOate as a positive control (50 μM) and determined p21 protein levels by Western blotting after 24 hours.…”
Section: Figurementioning
confidence: 67%
“…This finding is in agreement with previous reports indicating that in certain circumstances, stimulation of the MAPK pathway can induce p21 and lead to cell cycle arrest (23,29). Of particular relevance is the report by Bauer et al (37) who also observed an inhibition of DFMO-induced p21 up-regulation with the MEK inhibitors PD98059 and U0126 in rat aortic smooth muscle cells. At variance with our findings, however, these authors observed a reversal of the antiproliferative effects of DFMO with these two compounds.…”
Section: Discussionmentioning
confidence: 90%
“…This activity of NO ⅐ has been ascribed to both cGMP-dependent and -independent mechanisms. Experiments in rodents have found, with a few notable exceptions (18,30), that NO ⅐ controls the cell cycle through cGMP. In contrast, the anti-proliferation effects of NO ⅐ in human cells have been more frequently associated with cGMP-independent signaling (29,31).…”
Section: Discussionmentioning
confidence: 99%